Acrylic acid modified organic silicon and UV (ultraviolet) adhesive composition for difficult-to-adhere materials
By using linear phosphorus chloride eye catalyst in UV glue for rearrangement reaction of acrylic modified polydimethylsiloxane, the problem of insufficient bonding strength of existing UV glue to low-surface energy substances is solved, and high efficiency is achieved. Environmentally friendly bonding effect.
Patent Information
- Application Number
- CN202411446517.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-18
AI Technical Summary
The existing UV glue does not have sufficient bonding strength for low-surface energy substances (such as PE, PP, PET, POE, etc.), and traditional hot melt adhesives have shortcomings in heat resistance, making it difficult to widely use in the electronic and electrical industry.
Linear phosphorus chloride eye catalyst is used to generate acrylic modified polydimethylsiloxane through rearrangement reaction, forming high molecular weight acrylic modified polydimethylsiloxane, and is photoinduced with acrylate monomer and radicals. UV glue is formed by agents.
It achieves excellent bonding strength to low-surface energy substances, avoids tedious steps in traditional technology that require surface treatment, improves production efficiency, and reduces process costs.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ultraviolet (UV) curing adhesives, and in particular relates to a UV adhesive composition having good adhesion and bonding strength to difficult-to-bond materials. Background Art
[0002] The bonding of low surface energy materials (such as PE, PP, PET, POE, etc.) has always been a difficult problem and pain point in the adhesive industry. These materials are generally considered to be difficult to bond. Although hot melt adhesives have been developed for these low surface energy materials, hot melt adhesives themselves are thermoplastic resins, and their use temperature is difficult to exceed 100°C, which greatly limits their application in the electronic and electrical industry that requires heat resistance.
[0003] UV glue (ultraviolet curing adhesive) is increasingly favored by the industry because of its fast curing speed, energy saving and environmental protection, especially in the assembly line of electronic components. UV glue can be cured in seconds, the assembly speed of the production line can be greatly accelerated, and the use of UV glue can greatly improve production efficiency. The oligomers used in UV glue usually have more than two functional groups, can form a cross-linked network, and have good heat resistance. Therefore, UV glue is used for potting and bonding of many electronic components. However, UV glue composed of ordinary polyurethane acrylate compounds does not have sufficient bonding strength for low surface energy materials, and the cationic curing system of alicyclic epoxy resin does not have good adhesion to these materials. To obtain good bonding strength, the surface of the material must be physically treated (mechanical grinding and roughening of the surface, short-wavelength ultraviolet irradiation, corona, plasma treatment, etc.) or chemically treated (silane coupling agent, primer, etc.). Sometimes, even if the surface treatment is performed, sufficient bonding strength cannot be obtained. These treatment projects are not only time-consuming and labor-intensive, but also increase the process cost and pollute the working environment. Therefore, the industry has been looking for a UV glue that can be directly applied without surface treatment.
[0004] Japanese patent (Japanese Patent No. 2008-31307) discloses a photocurable organosiloxane composition, which has good bonding strength to PET, PBT, PC, ABS, and LCP (liquid crystal polymer). The synthesis method is to use terminal hydroxyl polydimethylsiloxane (107 silicone oil) and aminosilane coupling agent for dealcoholization reaction, and then react with 2-isocyanatoethyl methacrylate to form methacryloyloxy-terminated polydimethylsiloxane, and combine with some acrylate monomers compatible with organosilicon to form UV glue. The shear strength of PET / PET can reach 2.8MPa, which basically meets the bonding strength requirements of most applications. However, the price of this 2-isocyanatoethyl methacrylate monomer is very expensive, resulting in the high price of the synthesized methacryloyloxy-terminated polydimethylsiloxane, which can only be used for high-end applications. In addition, this methacryloyloxy-terminated polydimethylsiloxane has a fatal flaw. After long-term storage, it will undergo trace hydrolysis to produce a foul-smelling substance. Customers will feel very uncomfortable during use, and no effective solution has been found so far. Summary of the invention
[0005] The object of the present invention is to provide a UV curing adhesive for difficult-to-bond materials (such as PE, PP, PET, POE, etc.).
[0006] The technical solution to achieve the purpose of the present invention is:
[0007] In a first aspect, the present invention provides an acrylic modified polydimethylsiloxane having the following structure:
[0008] Wherein n=an integer from 40 to 2000.
[0009] In a second aspect, the present invention provides a method for synthesizing the acrylic acid-modified polydimethylsiloxane described in the first aspect, comprising:
[0010] The first step is to use a hydrogen-containing double-capped compound (tetramethyldisiloxane) and trimethylolpropane monoallyl ether to carry out a hydrosilylation reaction in the presence of a platinum catalyst to generate a double-capped compound containing two hydroxyl groups at both ends.
[0011]
[0012] The second step is to carry out an esterification dehydration reaction of a double-capped compound containing two hydroxyl groups at each end and an excess of acrylic acid in the presence of an acidic catalyst and a cyclohexane water-carrying agent to generate a double-capped compound ATH with two acryloyloxy structures at each end.
[0013]
[0014] The third step: a step of performing a rearrangement reaction between ATH and polydimethylsiloxane in the presence of a linear phosphine chloride catalyst to obtain a high molecular weight acrylic acid modified polydimethylsiloxane;
[0015]
[0016] Preferably, in order to prevent the self-polymerization of acrylic acid during the esterification and dehydration reaction of acrylic acid, a free radical inhibitor needs to be added during the esterification and dehydration reaction, and the amount added is 0.01% to 1% of the total mass of the reactants.
[0017] Specifically, the free radical inhibitor is any one or more of p-methoxyphenol, hydroquinone, 2,5-dimethylhydroquinone, and 2,6-di-tert-butyl-4-methylphenol.
[0018] Preferably, the acidic catalyst for the acrylic acid esterification dehydration reaction is selected from any one of concentrated sulfuric acid, sodium bisulfate, methanesulfonic acid, toluenesulfonic acid, trifluoromethanesulfonic acid, a strong acid ion exchange resin and a solid super acid, preferably any one of methanesulfonic acid, trifluoromethanesulfonic acid, a strong acid ion exchange resin and a solid super acid, and the added amount is 0.1% to 5.0% of the total mass of the reactants.
[0019] Preferably, the amount of linear phosphonium chloride catalyst added is 0.005-1.0% of the total amount of reactants.
[0020] Preferably, after the rearrangement reaction is completed, a passivating agent is used to inactivate the linear phosphonium chloride, and the amount of the passivating agent added is 1.1 to 4.0 times the amount of the linear phosphonium chloride added.
[0021] Specifically, the passivating agent can be selected as follows: First, amine compounds, such as triethylamine, propylamine, triethylnonylamine, hexamethyldisilazane, hexamethylcyclotrisilazane, etc. Second, lithium salts, n-butyl lithium n-hexane solution, hexamethyldisilazane lithium salt, trimethylsiloxy lithium, polydimethylsiloxane alkali glue of lithium hydroxide, etc. can be selected. Third, epoxy compounds, compounds containing more than one epoxy group in the molecule such as propylene oxide, glycidyl ether, bisphenol A diglycidyl ether, phenyl glycidyl ether, cyclohexene oxide, etc. can be selected. Fourth, salts of magnesium, aluminum, calcium, zinc, barium, and sodium, magnesium oxide, magnesium carbonate, magnesium hydroxide, aluminum oxide, zinc oxide, barium carbonate, sodium carbonate, etc. are selected. Triethylamine and hexamethyldisilazane are preferred.
[0022] In a third aspect, the present invention provides a UV adhesive composition for difficult-to-bond materials comprising the acrylic modified polydimethylsiloxane described in the first aspect, which comprises, by weight, 100 parts of acrylic modified polydimethylsiloxane, 10 to 80 parts of acrylate monomers and 0.5 to 5.0 free radical photoinitiators.
[0023] Preferably, the acrylate monomer is selected from any one or two of isobornyl acrylate (IBOA), cyclohexyl acrylate, tetrahydrofuranyl acrylate (THFA), tricyclodecyl acrylate, dicyclopentadiene acrylate, acryloyl morpholine (ACMO) and N,N-dimethylacrylamide (DMAA), preferably isobornyl acrylate, tetrahydrofuranyl acrylate (THFA), acryloyl morpholine (ACMO) and N,N-dimethylacrylamide (DMAA).
[0024] Preferably, the free radical photoinitiator is selected from 2-hydroxy-2-methylphenylacetone (Darocure 1173), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L), a mixture of 2,4,6-trimethylbenzophenone and 4-methylbenzophenone, benzoin dimethyl ether, benzophenone (BP), 1-hydroxy-cyclohexyl benzophenone, α,α′-ethoxyacetophenone (DEAP) or α-aminoalkylphenone, or a mixture of several thereof.
[0025] Preferably, based on the consideration of water resistance, the UV adhesive composition for the difficult-to-bond material may also be added with various epoxy silane coupling agents, titanate coupling agents, zirconate coupling agents, aluminate coupling agents, etc.
[0026] Preferably, the UV adhesive composition for difficult-to-bond materials further includes hydrophobic silica.
[0027] Compared with the prior art, the advantages of the present invention are:
[0028] (1) The present invention adopts a linear chlorinated phosphinothionine catalyst, and the ATH double end is subjected to rearrangement reaction with polydimethylsiloxane in the presence of the linear chlorinated phosphinothionine catalyst to obtain a high molecular weight acrylic acid modified polydimethylsiloxane. The reaction conditions are mild, the reaction speed is relatively fast, and no siloxane ring body is produced during the entire reaction process, and the volatile matter is extremely small, which well solves the problems of low activity of the target product of the traditional acid-catalyzed equilibrium reaction, low content of effective ingredients, residual low-boiling substances and many ring bodies. The cumbersome process of high vacuum and long-term high-temperature devolatilization with nitrogen gas in the later stage of the reaction is eliminated.
[0029] (2) The UV-curable acrylic modified silicone adhesive composition of the present invention has excellent bonding strength to low surface energy materials (such as PE, PP, PET, POE, etc.). DETAILED DESCRIPTION
[0030] The present invention is described in detail below with reference to the embodiments.
[0031] An effective method for connecting (meth)acryloyloxy groups to both ends of polydimethylsiloxane is to utilize the hydrosilylation reaction. First, terminal hydrogen-containing silicone oil and a bifunctional compound having an allyl group and an epoxy group or a hydroxyl group are subjected to hydrosilylation to generate a polydimethylsiloxane having a terminal epoxy group or a hydroxyl group structure. Then, the polydimethylsiloxane having a terminal epoxy group or a hydroxyl group structure is reacted with (meth)acrylic acid to introduce the (meth)acryloyloxy groups into the terminal groups of the polydimethylsiloxane, thereby making it have photocuring properties.
[0032] The purpose of the present invention is to connect two acryloyloxy functional groups to each end of polydimethylsiloxane, so that its photocurability is better than that of polydimethylsiloxane with one acryloyloxy structure at each end. In particular, for high molecular weight polydimethylsiloxane, if there is only one acryloyloxy group at the end group, the photocurability will be weakened due to the very small proportion of photocurable functional groups. If there are two acryloyloxy groups at each end group, the photocurability will be greatly improved, the crosslinking density will be higher, and the bonding strength will be correspondingly greater.
[0033] If a terminal hydrogen silicone oil (high molecular weight terminal hydrogen silicone oil) with extremely low hydrogen content is directly used as the initial reaction raw material and trimethylolpropane monoallyl ether is used to synthesize a high molecular weight terminal functional silicone oligomer, the SiH content is too low, resulting in an incomplete silane addition reaction, that is, less active substances are connected to the terminal group, which is not conducive to the next step of the reaction to obtain a silicone oligomer with good photocurability. In addition, trimethylolpropane monoallyl ether and low hydrogen silicone oil (that is, high molecular weight terminal hydrogen silicone oil) have poor compatibility, and the reaction is difficult to carry out. The common method in the industry is to use the silane addition reaction to synthesize a low molecular weight terminal active polydimethylsiloxane, and then extend the chain through the D4 equilibrium polymerization reaction to obtain a high molecular weight terminal active polydimethylsiloxane. That is, in order to obtain a high molecular weight acrylic modified polydimethylsiloxane, the ATH double head can be heated to 80°C in the presence of an acidic catalyst by adding a D4 ring body (octamethylcyclotetrasiloxane) for polymerization. However, this reaction is a balanced reaction. When the D4 conversion rate reaches 85-88wt%, the conversion rate cannot be further increased. Therefore, after the reaction is completed, 12-15%wt% of the ring body will remain and need to be removed by devolatilization under high vacuum. If the acidic catalyst inside is not removed cleanly at this time, the high molecular weight polydimethylsiloxane will also produce a reverse reaction in a high temperature acidic environment to generate D4 ring body, resulting in more and more D4 ring body being degraded during the devolatilization process. Therefore, the acidic catalyst must be neutralized with sodium carbonate, washed with water and dried before devolatilization. These complicated operation processes not only increase production costs and reduce production efficiency, but also reduce product yields.
[0034] To this end, the present invention first synthesizes a double-capped agent ATH with two acryloyloxy groups at each end, and then carries out a rearrangement reaction with polydimethylsiloxane in the presence of a linear chlorinated phosphine catalyst to obtain a high molecular weight acrylic acid modified polydimethylsiloxane. By adjusting the dosage ratio of ATH double-capped and polydimethylsiloxane, products of different molecular weights can be obtained. The more the amount of ATH double-capped is used, the smaller the molecular weight obtained, and the more the amount of polydimethylsiloxane is used, the larger the molecular weight obtained. During the entire reaction process, no siloxane ring body is produced, and the volatile matter is very small, which well solves the problems of low activity of the target product of the traditional acid-catalyzed equilibrium reaction, low content of effective ingredients, residual low-boiling substances and many ring bodies. After the reaction is completed, a passivating agent is used to inactivate the linear chlorinated phosphine.
[0035] Synthetic acrylic modified polydimethylsiloxane is combined with acrylate monomers, free radical photoinitiators, coupling agents, and hydrophobic silica to form a UV adhesive with excellent bonding strength to low surface energy materials.
[0036] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0037] The following is a detailed introduction to the synthesis and formulation examples of acrylic modified polydimethylsiloxane.
[0038] Synthesis of dihydroxy double capping agent.
[0039] Add 100g trimethylolpropane monoallyl ether and 0.01g chloroplatinic acid into a three-necked glass flask with an oil bath and a condenser, stir and heat to 70°C, add 42g hydrogen-containing double-capping agent (1,1,3,3-tetramethyldisiloxane) dropwise, and complete the addition within one hour, then heat to 80°C and continue the reaction for 4h, remove the unreacted hydrogen-containing double-capping agent in vacuo, and obtain a colorless and transparent double-capping agent (double hydroxyl double-capping agent) with two hydroxyl groups at each end. The molecular weight is 482.7.
[0040] Synthesis of bisacryloxy double capping agent (ATH synthesis).
[0041] Add 100g of dihydroxy double-capping agent, 66g of acrylic acid, 6.0g of methylsulfonic acid, 0.06g of MeHQ free radical inhibitor, and 150g of cyclohexane water-carrying agent into a three-necked glass flask with an oil bath and condenser, stir and heat to 85°C for reflux, and regularly release the water brought out with a separatory tube, carefully observe the amount of water retained in the separatory tube until no more excess water is distilled out, and the reaction is considered complete. Cool to room temperature, add excess sodium carbonate to neutralize the residual acrylic acid and acidic catalyst, precipitate and filter, wash with water several times, and then vacuum dry to obtain a light yellow transparent double-capping agent with two acryloyloxy groups at each end, referred to as ATH, with a viscosity of 420mPas and a molecular weight of 698.7.
[0042] Modified silicone synthesis example-1.
[0043] In a three-necked glass flask with an oil bath and a condenser, add 85g of polydimethylsiloxane with a viscosity of 1000mPas and 0.1g of linear phosphine chloride catalyst, stir and heat to 80°C under nitrogen protection, gradually add 10g of double-capping agent ATH, and complete the addition within one hour, then heat to 110°C and continue to react for 4h, cool to room temperature, add 0.2g of triethylamine passivator, and obtain colorless and transparent polydimethylsiloxane with two acryloyloxy groups at each end, with a molecular weight of about 6600. The product is named Modified Silicone Synthesis Example-1.
[0044] Modified silicone synthesis example-2.
[0045] Add 1000g polydimethylsiloxane with a viscosity of 500mPas and 0.5g linear chlorophosphine catalyst into a three-necked glass flask with an oil bath and a condenser, stir and heat to 80°C, gradually add 19g double-capping agent ATH, and complete the addition within one hour, then heat to 110°C and continue to react for 4h, cool to room temperature, add 1.0g hexamethyldisilazane passivator, and obtain colorless and transparent polydimethylsiloxane with two acryloyloxy groups at each end, with a molecular weight of about 37000. The product is named Modified Silicone Synthesis Example-2.
[0046] The formulations of the embodiments and comparative examples are shown in Table 1 below.
[0047] Table 1
[0048] Example-1 Example-2 Example-3 Example-4 Comparative Example-1 Comparative Example-2 Comparative Example-3 Comparative Example-4 Modified silicone synthesis example-1 100 100 Modified silicone synthesis example-2 100 100 100 Baojun Chemical 2900 100 Zhongshan Qianyou 3001 100 100 IBOA 40 40 40 30 40 40 40 DMAA 5 5 5 ACMO 5 5 5 5 THFA 5 10 5 TS720 20 25 20 15 R970 20 15 15 15 Darocure1173# 2.0 2.0 2.0 2.0 2.0 2.0 2.0 2.0 TPO-L 1.0 1.0 1.0 1.0 1.0 1.0 1.0 1.0 KBM403 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 KBM5103 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Shear strength(MPa) PE / PE 0.9 1.2 1.3 1.5 0.4 0.3 0.4 0.5 PP / PP 1.8 2.6 2.8 2.9 1.1 0.5 0.9 1.0 PET / PET 2.2 3.2 3.2 3.5 1.0 2.5 2.7 2.6 POE / POE 2.9 3.8 4.2 5.1 0.9 0.9 1.1 1.2
[0049] Note: TS720 is Cabot hydrophobic silica from the United States; R970 is Evonik hydrophobic silica from Germany; KBM403 is Shin-Etsu γ-glycidyloxypropyl trimethoxysilane from Japan; KBM5103 is Shin-Etsu 3-(acryloyloxy)propyl trimethoxysilane from Japan; Baojun Chemical 2900 is a polyurethane type acrylate oligomer with good bonding strength to PET film; Zhongshan Qianyou 3001 is a polyurethane type acrylate oligomer with good bonding strength to PET film; IBOA is isobornyl acrylate; DMAA is N,N-dimethylacrylamide; ACMO is acryloylmorpholine; THFA is tetrahydrofuran acrylate; PE is polyethylene; PP is polypropylene; PET is polyethylene terephthalate; POE is polyolefin elastomer.
[0050] Preparation of shear strength test piece: Wipe the surface of the test piece with alcohol to remove the oil and dust on the surface. Fix it with a butterfly clip after gluing, and then cure it with ultraviolet light. The ultraviolet light dose is 1000mJ / cm on both sides. 2 , place at room temperature for 30 minutes to test the shear strength. The test method is in accordance with GB / T 7124-2008.
[0051] According to Table 1, by comparing Examples 1 to 4, it is found that the acrylic modified polydimethylsiloxane UV adhesive compounded with acrylate monomers shows good bonding strength for PE, PP, PET, POE, etc. However, Comparative Example 1 uses a single acrylic modified polydimethylsiloxane without compounding with acrylate monomers, and its bonding strength is relatively low. Comparative Examples 2 to 4 use commercially available polyurethane acrylate oligomers compounded with UV adhesives that have good bonding strength to PET films. Although they have good adhesion to PET films, their bonding strength to low surface energy materials such as PE, PP, POE, etc. is very low and does not meet practical requirements.
Claims
1. An acrylic acid-modified polydimethylsiloxane, characterized in that: It has the following structure: Wherein n=an integer from 40 to 2000.
2. A method for synthesizing acrylic acid-modified polydimethylsiloxane, characterized in that: include: The first step is to use a hydrogen-containing double-capped compound and trimethylolpropane monoallyl ether to carry out a hydrosilylation reaction in the presence of a platinum catalyst to generate a double-capped compound containing two hydroxyl groups at both ends. The second step is to carry out an esterification dehydration reaction of a double-capped compound containing two hydroxyl groups at each end and an excess of acrylic acid in the presence of an acidic catalyst and a cyclohexane water-carrying agent to generate a double-capped compound ATH with two acryloyloxy structures at each end. The third step is to carry out a rearrangement reaction between ATH and polydimethylsiloxane in the presence of a linear phosphine chloride catalyst to obtain a high molecular weight acrylic acid modified polydimethylsiloxane.
3. The method according to claim 2, characterized in that A free radical inhibitor is added in the esterification dehydration reaction, and the amount thereof added is 0.01% to 1% of the total mass of the reactants.
4. The method according to claim 3, characterized in that The free radical inhibitor is any one or more of p-methoxyphenol, hydroquinone, 2,5-dimethylhydroquinone and 2,6-di-tert-butyl-4-methylphenol.
5. The method according to claim 2, characterized in that The acidic catalyst for the acrylate dehydration reaction is selected from any one of concentrated sulfuric acid, sodium bisulfate, methanesulfonic acid, toluenesulfonic acid, trifluoromethanesulfonic acid, strongly acidic ion exchange resin and solid super acid, preferably any one of methanesulfonic acid, trifluoromethanesulfonic acid, strongly acidic ion exchange resin and solid super acid, and the added amount is 0.1% to 5.0% of the total mass of the reactants.
6. The method according to claim 2, characterized in that The amount of linear phosphonium chloride catalyst added is 0.005-1.0% of the total amount of reactants.
7. The method according to claim 2, characterized in that After the rearrangement reaction is completed, a passivating agent is used to inactivate the linear phosphonium chloride, and the amount of the passivating agent added is 1.1 to 4.0 times the amount of the linear phosphonium chloride added.
8. A UV adhesive composition for difficult-to-bond materials, characterized in that: The invention comprises, by weight, 100 parts of the acrylic modified polydimethylsiloxane according to claim 1, 10 to 80 parts of acrylate monomers and 0.5 to 5.0 parts of free radical photoinitiator.
9. The UV adhesive composition according to claim 8, characterized in that: The acrylate monomer is selected from any one or two of isobornyl acrylate (IBOA), cyclohexyl acrylate, tetrahydrofuranyl acrylate (THFA), tricyclodecyl acrylate, dicyclopentadiene acrylate, acryloyl morpholine (ACMO) and N,N-dimethylacrylamide (DMAA), preferably any one or two of isobornyl acrylate, tetrahydrofuranyl acrylate (THFA), acryloyl morpholine (ACMO) and N,N-dimethylacrylamide (DMAA).
10. The UV adhesive composition according to claim 8, characterized in that: The free radical photoinitiator is selected from 2-hydroxy-2-methylphenylacetone (Darocure 1173), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L), a mixture of 2,4,6-trimethylbenzophenone and 4-methylbenzophenone, benzoin dimethyl ether, benzophenone (BP), 1-hydroxy-cyclohexyl benzophenone, α,α′-ethoxyacetophenone (DEAP) or α-aminoalkyl phenone. One or a mixture of several.
Citation Information
Patent Citations
Photocurable organopolysiloxane composition
JP2008031307A
Preparation method of vinyl silicone oil with medium and low viscosity
CN117777452A
(Methyl) acrylic modified polysiloxane and synthesis method thereof
CN117887079A
UV (ultraviolet) adhesive for difficult-to-adhere materials
CN119081641A
Photocurable silicone composition for hardly adherable material
JP2002302664A